Critical Reflective Practice as an Approach to Developing Transformative Living-theory - Qutoshi, Sadruddin Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2018)
This reflective paper aims to provide an opportunity to the readership in the field of transformative education in order to engage them with reflective practices as professional development approach. In academia, writing reflective papers, using multi-paradigmatic research design, for readers believing in post/positivist views is a challenging task. However, innovative editors of journals encourage to create new knowledge through un/conventional approaches. I used Jack Whitehead’s paper (i.e., the review of my doctoral study- Creating living-educational-theory: A journey towards transformative teacher education in Pakistan) and my own reflections as lived experiences to carry out this study. Moreover, I employed reflexivity as an approach to meaning making to serve the purpose of data analysis in this paper. The key findings of this study show that Jack Whitehead skillfully captures key learning outcomes of the doctoral study and synthesized some deep insights very precisely. He created a space for future researchers especially action researches and self-study practitioners to think about how to engage with multi-epistemic approaches in order to experience transformative learning. It is recommended to encourage reflective writings on un/conventional studies to develop a clear understanding of the existing state of teacher education and nature of the journey of transformative teacher education in the academia.